2012
DOI: 10.1371/journal.pone.0041399
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan Derived from Aureobasidium pullulans Is Effective for the Prevention of Influenza in Mice

Abstract: β-(1→3)-D-glucans with β-(1→6)-glycosidic linked branches produced by mushrooms, yeast and fungi are known to be an immune activation agent, and are used in anti-cancer drugs or health-promoting foods. In this report, we demonstrate that oral administration of Aureobasidium pullulans -cultured fluid (AP-CF) enriched with the β-(1→3),(1→6)-D-glucan exhibits efficacy to protect mice infected with a lethal titer of the A/Puerto Rico/8/34 (PR8; H1N1) strain of influenza virus. The survival r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 52 publications
5
56
0
Order By: Relevance
“…We have also shown that there is a differential expression profile where for example tlr3.1 was primarily up-regulated in the spleen, head kidney and mid gut whilst tlr3.2 was up-regulated in the head kidney and mid gut. We suggest that the up-regulation of tlr3 genes may explain why the injection of poly(I:C) specifically increased the expression levels of mx among other cytokines analysed, which is in concordance with reported increases of protection against viral pathogens conferred by β-glucan compounds in fish [9] and [10] and mammals [42]. Further assays on the expression levels of other virus sensing receptors in response to β-glucan and/or the functional groups from β-glucan with this activity are required to better understand the immunological activities of this immunostimulant and its role in virus defense.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We have also shown that there is a differential expression profile where for example tlr3.1 was primarily up-regulated in the spleen, head kidney and mid gut whilst tlr3.2 was up-regulated in the head kidney and mid gut. We suggest that the up-regulation of tlr3 genes may explain why the injection of poly(I:C) specifically increased the expression levels of mx among other cytokines analysed, which is in concordance with reported increases of protection against viral pathogens conferred by β-glucan compounds in fish [9] and [10] and mammals [42]. Further assays on the expression levels of other virus sensing receptors in response to β-glucan and/or the functional groups from β-glucan with this activity are required to better understand the immunological activities of this immunostimulant and its role in virus defense.…”
Section: Discussionsupporting
confidence: 89%
“…RIG-I and MDA5, occurred 5 h after stimulation with β-glucan purified from Aureobasidium pullulans. Moreover, pre-treatment with this β-glucan compound conferred protection against the A/Puerto Rico/8/34 (PR8; H1N1) strain of influenza virus in vitro (RAW264.7 cells) and in vivo in orally administered mice [42]. Altogether, these results suggest an evolutionary conserved protective activity of β-glucans by means of increasing the sensitivity of treated cells to viral components.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Isolates F-3 through F-99 and the remaining 25 isolates were not related to Group I. Generally, A. pullulans produces polysaccharides, including pullulan and β-glucan, which find industrial and medical applications (Yurlova and de Hoog, 1997;Cheng et al, 2011;Muramatsu et al, 2012). Recently, A. pullulans has been shown to produce (poly)malic acid (Nagata et al, 1993), lipase , laccase (Rich et al, 2011), mannitol oils (Price et al, 2013), biocontrol agents (Mari et al, 2012), biosurfactants , valuable lipids (Turk et al, 2004), and siderophores (Ma et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Murine macrophageAureobasidium pullulans (Muramatsu et al, 2012) Ddx58 is RIG-1 (retinoic acid-IL-6, TNFα, GM-CSF derived RAW264.7 cells produced purified β (1->3), inducible gene-I). MDA5 is an and G-CSF…”
Section: Rela Relb Nfkb2 Nfkb1 Eb13 Cflar Btg1 Basp1 Atf4 Aimentioning
confidence: 99%